Saskia Becker: capstone - Becker, Saskia, artist (Colorado State University. Libraries, 2019)
The artist's statement: Through the medium of painting, I am exploring the subconscious and the phenomenon of dreaming. As an artist, I am intrigued by the endless labyrinths in the universe and my mind. My dreams will often inform and inspire my work; I like to think of them as divine gifts from the Universe. In a sense, creating art has become an act of gratitude. As I dig deep into these spaces that seem to hold no logic, I have discovered dreams are inextricably paired with the subconscious. According to the late Swiss psychologist, Carl Jung, dreams are thought to be the vehicle of communication from the subconscious to the conscious mind. Archetypal symbols are used by the subconscious as a way of expressing universally understood ideas or feelings in all human dreams. In my practice I am continually questioning the symbols and narratives that enter my dreams to better understand what my subconscious and spiritual mind is expressing. I start many mornings reaching over to grab my journal and scribble down what I remember from the night before they slip away into the abyss. Some aspects of my dreams stand out vividly, whether that be a person, object, or a place . . . they make an impression. I make note of these symbols and then construct my paintings around them. In this way, my paintings are a method of deeply understanding, honoring, and appreciating the remarkable presence of my dreams. My dream paintings are catered to my life, yet their messages often transcend individuality, speaking to the human collective consciousness. By tapping into these possibilities, I have discovered that when I visually manifest my dreams, I am participating and replying in a universal dialogue that is overwhelmingly mystifying and magical.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing